Evaluating selected forage legumes for livestock and crop production in the subhumid zone of Nigeria - Tarawali, Shirley A. (Cambridge University Press, 1994)
A programme of forage legumes evaluation was developed at ILCA subhumid research site in Nigeria from 1985 onwards. Evaluation included monitoring herbage and seed yields, incidence of diseases/pests, regeneration ability and persistence for three growing seasons. This was followed by an in six bioassar to determine the direct effect of the sown legumes on maize (zea mays L.) aproduction in the absence of added nitrogen. The results for selected accessions from introductions received in 1987 and 1988 are presented. Stylosanthes guianensis and Aeschynomene histrix were promissing both in terms of biomass production and quality, and in terms of beneficial effects for maize production. The use of such appropriate forage legumes to enhance both livestock and crop production in a sustainable farming system is recommended.